Governmental taxation of households choosing between a national currency and a cryptocurrency - Guizhou Wang; Kjell Hausken (Games, 2021)
A game between a representative household and a government was analyzed. The household chose which fractions of two currencies to hold, e.g., a national currency such as a Central Bank Digital Currency (CBDC) and a global currency such as Bitcoin or Facebook's Diem, and chose the tax evasion probability for each currency. The government chose, for each currency, the probability of detecting and prosecuting tax evasion, the tax rate, and the penalty factor imposed on the household when tax evasion was successfully detected and prosecuted. The household′s fraction of the national currency, the government's monitoring probability of the national currency, and the penalty factor imposed on the global currency, increased in the household′s Cobb Douglas output elasticity for the national currency. The household′s probabilities of tax evasion on both currencies increased in the government's Cobb Douglas output elasticity for the national currency. The government's taxation on both currencies decreased in the output elasticity for the national currency. High output elasticity for the national currency eventually induced the government to tax that currency more than the global currency. The household′s probability of tax evasion on the global currency increased in the government's output elasticity for that currency. The household was less (more) likely to tax evade on the national (global) currency if the government valued taxation and penalty on the national (global) currency. The results are illustrated numerically where each of the eight parameter values were varied relative to a benchmark.
Keywords: C72; H26; 330; Bitcoin; CBDC; cryptocurrency; digital currency; game theory; government; household; taxation